Tensile energy dissipation and mechanical properties of the knee meniscus: relationship with fiber orientation, tissue layer, and water content - Morejon, Andy; Dalbo, Pedro L.; Best, Thomas M.; Jackson, Alicia R.; Travascio, Francesco (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The knee meniscus distributes and dampens mechanical loads. It is composed of water (∼70%) and a porous fibrous matrix (∼30%) with a central core that is reinforced by circumferential collagen fibers enclosed by mesh-like superficial tibial and femoral layers. Daily loading activities produce mechanical tensile loads which are transferred through and dissipated by the meniscus. Therefore, the objective of this study was to measure how tensile mechanical properties and extent of energy dissipation vary by tension direction, meniscal layer, and water content. Methods: The central regions of porcine meniscal pairs (n = 8) were cut into tensile samples (4.7 mm length, 2.1 mm width, and 0.356 mm thickness) from core, femoral and tibial components. Core samples were prepared parallel (circumferential) and perpendicular (radial) to the fibers. Tensile testing consisted of frequency sweeps (0.01–1Hz) followed by quasi-static loading to failure. Dynamic testing yielded energy dissipation (ED), complex modulus (E*), and phase shift (δ) while quasi-static tests yielded Young’s Modulus (E), ultimate tensile strength (UTS), and strain at UTS (εUTS). To investigate how ED is influenced by the specific mechanical parameters, linear regressions were performed. Correlations between sample water content (φw) and mechanical properties were investigated. A total of 64 samples were evaluated. Results: Dynamic tests showed that increasing loading frequency significantly reduced ED (p < 0.05). Circumferential samples had higher ED, E*, E, and UTS than radial ones (p < 0.001). Stiffness was highly correlated with ED (R2 > 0.75, p < 0.01). No differences were found between superficial and circumferential core layers. ED, E*, E, and UTS trended negatively with φw (p < 0.05). Discussion: Energy dissipation, stiffness, and strength are highly dependent on loading direction. A significant amount of energy dissipation may be associated with time-dependent reorganization of matrix fibers. This is the first study to analyze the tensile dynamic properties and energy dissipation of the meniscus surface layers. Results provide new insights on the mechanics and function of meniscal tissue.